Financial Management Plan for IT Service at PPTI Stikom Surabaya using ITIL V3 - Prasetianto, Andreas Yanuar; Amelia, Tan; Sutomo, Erwin (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
Pengembangan dan Penerapan Teknologi Informasi (PPTI) is one part in theInstitute of Business and Information Stikom Surabaya (Surabaya Stikom). PPTI main objective isto develop and apply information technology as an integral part in the learning process and serviceboth in academic and non-academic civitas all, and in the process of achieving the vision andmission of PPTI must have good planning includes financial planning where financial planning willbe used by PPTI in the process of fulfilling the needs of the technology services needed by societymembers Stikom Surabaya. To clarify the direction and financial objectives of PPTI, we conductedresearch with reference to the standard Service Strategy in the framework of the InformationTechnology Infrastructure Library (ITIL v3).This research resulted in financial documents thatcontain document management cost models, business case, budget planning, as well as the cost ofeach service policy that eventually all the documents will be useful for PPTI.